Study of interaction of uranyl ion with diethyl ester 2,2′-(1H-1,2,4-triazole-3,5-diyl)diacetate - Vaschenko, O.V.; Khomenko, D.M.; Doroschuk, R. O.; Lampeka, R.D. (Reports of the National Academy of Sciences of Ukraine, 2015)
The study of the interaction of uranyl ion with diethyl 2,2′-(1H-1,2,4-triazole-3,5-diyl)diacetate is undertaken, and the obtained uranyl complex with 2,2′-(1H-1,2,4-triazole-3,5-diyl)-diacetic acid has been studied by means of NMR and IR spectroscopy. It is shown that the initial organic ligand undergoes hydrolysis under the conditions described and forms complex UO22+ : L2− = 1 : 1, where L2− is the dianion of 2,2′-(1H-1,2,4-triazole-3,5-diyl)-diacetic acid. It is supposed that uranyl ions catalyze the hydrolysis process.